Experience of a Single Center in Treating Multiple Manifestations of Tuberous Sclerosis Complex with Everolimus - Hyunji Ahn; Mi-Sun Yum; Han Na Jang; Cheryn Song; Tae-Sung Ko (Annals of Child Neurology, 2019)
Purpose The aim of this study was to evaluate the efficacy and tolerability of everolimus, an oral mammalian target of rapamycin (mTOR) inhibitor, for the treatment of tuberous sclerosis complex (TSC) manifestations. Methods A retrospective analysis was conducted using an in-house research database with the keywords “tuberous sclerosis AND everolimus.” Twenty patients were treated with everolimus for TSC from 2013 to February 2019. Results The mean age of the 20 patients was 25.6 years (range, 0 to 57), and the average duration of everolimus treatment was 87.6 weeks (range, 0 to 290). Everolimus was given with a usual daily dosage of 5 to 10 mg (mean, 7.1) or 0.0625 to 0.5 mg for neonates. Twelve patients were prescribed everolimus for more than 1 year for kidney angiomyolipoma (AML). Two of those patients (16.7%) experienced reductions of >50% in tumor size, and four patients (33.3%) experienced reductions of 25% to 50%. The four patients who were prescribed everolimus for subependymal giant cell astrocytoma (SEGA) had 25% to 50% reductions. Neonates with cardiac rhabdomyoma showed significant tumor reduction with everolimus, but their tumors exhibited rebound size increases after treatment was halted. Of the three patients with intractable seizures, one patient became seizure-free, and two patients had >50% reductions. Overall, everolimus therapy was well tolerated. Conclusion Everolimus, an mTOR inhibitor, was effective for seizure control and size reduction of kidney AML, SEGA, and cardiac rhabdomyoma tumors in patients with TSC. However, clinicians should also be aware of the adverse event profile of everolimus.